EXISTENCE AND UNIQUENESS THEOREM FOR A SOLUTION OF FUZZY IMPULSIVE DIFFERENTIAL EQUATIONS - Ramesh, R.; Vengataasalam, S. (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, we prove the existence and uniqueness of a solution of the fuzzy impulsive differential equation x′(t) = f(t,x(t)), x(t0) = x0, ∆x(tk) = Ik(x(tk)) by using the method of successive approximation. We also consider the ϵ-approximate solution for the above fuzzy impulsive differential equation.